KANDUNGAN ASAM ASKORBAT PADA KULTUR KALUS ROSELA (hibiscus sabdariffa L.) DENGAN VARIASI KONSENTRASI SUKROSA DALAM MEDIA MS - Yulita Nurchayati; Fathiyah Afiah R (Faculty of Pharmacy, Universitas Gadjah Mada, 2010)
Ascorbic acid is an antioxidant which is found in rosella flower. Its production through conventional method needs long time and wide field, so an alternative method through development of callus invitro is conducted. Sucrose is a main carbon source in MS medium and this sugar plays role as precursor for the formation of ascorbic acid. This study was conducted to determine the effect of sucrose concentration on callus formation and production of ascorbic acid. Sucrose was added to the media at the concentration of 20 g/L, 30 g/L, 40 g/L and 50 g/L. The culture was incubated for 42 days with twice subculture every 10 days. Analysis of ascorbic acid was perfomed using iodometry. The results showed that the callus was grow better in sucrose of 20 g/L while the ascorbic acid production was better in sucrose 50 g/L.